Analysis of The Influence of Good Corporate Governance on the Quality of Financial Reports - Astrid Tabita; Renny Maisyarah (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This study aims to analyze the impact of Good Corporate Governance (GCG) on the quality of financial reports in companies. GCG plays a crucial role in ensuring transparency, accountability, and reliability in financial reporting, which is essential for investors, regulators, and stakeholders. The research employs a quantitative approach using financial data from publicly listed companies. Key GCG indicators, including board independence, audit committee effectiveness, managerial ownership, and institutional ownership, are examined to determine their influence on financial report quality. The study applies multiple regression analysis to evaluate the relationship between GCG practices and financial report quality, measured using earnings management indicators and financial disclosure levels. The results indicate that strong corporate governance mechanisms significantly enhance financial report quality by reducing earnings management practices and increasing financial transparency. Specifically, independent boards and effective audit committees contribute to higher-quality financial reporting. Managerial ownership has a moderate impact, while institutional ownership influences financial disclosure positively.